The theory‐based view: Entrepreneurial microfoundations, resources, and choices - Wuebker, Robert; Zenger, Todd; Felin, Teppo (Strategic Management Journal, 2023)
Abstract Research Summary We build on the theory‐based view and highlight how an entrepreneur's theory can enable the creation of value. We point to three types of theories: theories of resource arbitrage, resource recombination, or resource investment that specialize resources to particular uses. However, possessing a unique theory is not enough. The realization of an entrepreneur's theory is contingent on matching it with the right organizational and governance‐related choices. Entrepreneurs must make consequential decisions about protecting intellectual property, running experiments, acquiring resources, composing teams, and securing financing. We develop a contingent approach that enables entrepreneurs to match their theory of value with the appropriate forms of action, thereby providing entrepreneurs with a level of guidance to downstream choices that the current literature fails to provide. Managerial Summary To create economic value, entrepreneurs need to develop their own, unique theory of value. In this article, we highlight three distinct types of entrepreneurial theory and link these to value creation. We further point out how the realization of each theory of value depends on making the right downstream choices related to the protection of intellectual property, experimentation, resource acquisition, the composition of a team, and financing. Existing advice to entrepreneurs tends to offer one‐size‐fits‐all solutions (e.g., related to experimentation), while we argue that choices about how to pursue value creation should depend on the type of theory of value that an entrepreneur pursues.